Tandem anchoring informational and politeness effects of range offers in social exchange. [article]. - Ames, Daniel R.; Mason, Malia F.
We examined whether and why range offers matter in negotiations. A selective-attention account predicts that motivated and skeptical offer-recipients focus overwhelmingly on the attractive endpoint. In contrast, we propose a tandem anchoring account, arguing that offer-recipients are often influenced by both endpoints as they judge the offer-maker?s reservation price. As well as how polite they believe an extreme (nonaccomodating) counteroffer would be. In 5 studies, featuring scripted settlement terms for offer-makers without relational costs, whereas other may yield relationship benefits without deal costs. We clarify the type of range offers that evoke these benefits and identify boundaries to their impact, including range width and extremity. In addition, our studies reveal evidence consistent with 2 proposed mechanisms, one involving an informal effect (both endpoints of range offers can be taken as signals of an offer-maker?s reservation price) and another involving a politeness effect (range offers can make extreme counteroffers seem less polite). Our results have implications for models of negotiation behavior and outcomes and, more broadly, for the nature of social exchange. - - (from the authors)
Keywords: Social exchange-Periodicals.; Negotiation-Periodicals.; First offers-Periodicals.; Politeness-Periodicals.